Unit-segment Analysis: A Space Syntax Approach to Capturing Vehicular Travel Behavior Emulating Configurational Properties of Roadway Structures - Paul, Abhijit (European Journal of Transport and Infrastructure Research, 2012)
One of the critical concerns of axial analysis, a space syntax approach to capturing vehicular travel behavior emulating configurational properties of roadway structures, is the absence of the time-cost consideration while dealing with route-choice problems encountered in grid-like urban textures. This study shows that the time-cost parameter of travel can also be introduced into the syntax approach to capturing the route-choice decisions for the purpose of modeling vehicular movement networks with greater accuracy. Assuming that roadway units are trip-origins and trip-destinations and that they also act as connecting route segments among each other, a theoretical foundation has been proposed showing how the mobility characteristics of these units, in terms of the time-cost of travel, influence their accessibility measures or syntax integrations. These new roadway units are the unit segments, and their integrations are found to be better indicators of vehicular trip-makers’ route-choice decisions than axial integrations. Conclusions suggest that the unit-segment analysis of an urban grid captures the general behavior of vehicular flow by substantiating the fact that trip-makers tend to pick a specific set of roadway units that not only comprise the close connection between a triporigin and a trip-destination but also consume less time for travel.